HORTATORY AND ANALYTICAL EXPOSITION ANALYSIS ON STUDENT’S WRITING: Case Study of 2nd Semester University of Serang Raya Students - Mada, Ratu Dea; Fachriyah, Eva; Hasanah, Arifiatul (Journal of English Language Teaching and Literature (JELTL), 2022)
This research aims to identify how students at second semester in University of Serang Raya can differentiate between hortatory and Analytical Expositions. The method used is descriptive study. The sample of this research are 7 classes of second semester in University of Serang Raya. The tool for data collecting was a written text that students wrote in two kinds of text, Hortatory and Analytical Exposition in a side by side form (2 columns) and a quiz in a google forms. It is hope that by analysing the students’ writing, they are able to comprehend and differentiate the structure and the content of Hortatory and Analytical Exposition